Nitric Oxide Is Essential for Generating the Minute Rhythm Contraction Pattern in the Small Intestine, Likely via ICC-DMP - Parsons, Sean P.; Huizinga, Jan D. (Frontiers in Neuroscience, 2021)
Nitrergic nerves have been proposed to play a critical role in the orchestration of peristaltic activities throughout the gastrointestinal tract. In the present study, we investigated the role of nitric oxide, using spatiotemporal mapping, in peristaltic activity of the whole ex vivo mouse intestine. We identified a propulsive motor pattern in the form of propagating myogenic contractions, that are clustered by the enteric nervous system into a minute rhythm that is dependent on nitric oxide. The cluster formation was abolished by TTX, lidocaine and nitric oxide synthesis inhibition whereas the myogenic contractions, occurring at the ICC-MP initiated slow wave frequency, remained undisturbed. Cluster formation, inhibited by block of nitric oxide synthesis, was fully restored in a highly regular rhythmic fashion by a constant level of nitric oxide generated by sodium nitroprusside; but the action of sodium nitroprusside was inhibited by lidocaine indicating that it was relying on neural activity, but not rhythmic nitrergic nerve activity. Hence, distention-induced activity of cholinergic nerves and/or a co-factor within nitrergic nerves such as ATP is also a requirement for the minute rhythm. Cluster formation was dependent on distention but was not evoked by a distention reflex. Block of gap junction conductance by carbenoxolone, dose dependently inhibited, and eventually abolished clusters and contraction waves, likely associated, not with inhibition of nitrergic innervation, but by abolishing ICC network synchronization. An intriguing feature of the clusters was the presence of bands of rhythmic inhibitions at 4-8 cycles/min; these inhibitory patches occurred in the presence of tetrodotoxin or lidocaine and hence were not dependent on nitrergic nerves. We propose that the minute rhythm is generated by nitric oxide-induced rhythmic depolarization of the musculature via ICC-DMP.